Perforated Meckel's diverticulum by chicken bone associated with terminal ilial volvulus in a child - Alshaima Alghamdi; Enaam Raboei (Elsevier, 2020)
Foreign body ingestions are a common occurrence in children. The initial presentation can vary from the child being completely asymptomatic to a variety of symptoms. Perforation of Meckel's diverticulum by foreign bodies is a rare cause of acute abdomen. It is usually diagnosed intraoperatively.We herein report on an unusual case of a 3-year-old male child who came to the Emergency department with diffuse abdominal pain associated with bilious vomiting and diarrhea. The initial diagnosis was acute small bowel obstruction. After exploration, it turned out to be perforated Meckel's diverticulum caused by a swallowed chicken bone.